Moulting rates of Calanus helgolandicus: an inter-comparison of experimental methods - Shreeve, Rachael S; Ward, Peter; Murray, Alistair W.A (Journal of experimental marine biology and ecology, 1998)
An inter-comparison of three commonly reported methods for estimating the stage duration of copepods was made on Calanus helgolandicus from both wild and laboratory-reared populations. These three methods have not been compared previously in contemporaneous experiments. The methods were: (1) following the stage frequency of a laboratory-reared population over time, (2) sorting of individual species stages from the laboratory-reared population and from wild plankton samples, followed by incubation, and (3) sieve fractionating the wild plankton sample followed by incubation. We establish that estimates by these three methods made from the wild and laboratory-reared populations did not differ significantly. Handling of the animals did not affect estimates of moulting rate significantly, but there was a wide range in stage durations in identical copepodite stages which had experienced similar environmental conditions. We therefore suggest that the `Heinle' method would be most applicable to use on populations with a clear cohort structure in areas not subjected to high rates of advection, and which experience saturating food conditions. The sorted cohort method would be appropriate to areas which were subject to high rates of advection and to a population which had prolonged recruitment, but because this is a labour intensive method the sieved cohort method may be more appropriate when the plankton hauls are dominated by a particular species of copepod.